Nonpolar m-plane GaN/AlGaN heterostructures with intersubband transitions in the 5–10 THz band. (5th October 2015) - Lim, C B; Ajay, A; Bougerol, C; Haas, B; Schörmann, J; Beeler, M; Lähnemann, J; Eickhoff, M; Monroy, E
Abstract: This paper assesses intersubband (ISB) transitions in the 1–10 THz frequency range in nonpolar m -plane GaN/AlGaN multi-quantum-wells deposited on free-standing semi-insulating GaN substrates. The quantum wells (QWs) were designed to contain two confined electronic levels, decoupled from the neighboring wells. Structural analysis reveals flat and regular QWs in the two perpendicular in-plane directions, with high-angle annular dark-field scanning transmission electron microscopy images showing inhomogeneities of the Al composition in the barriers along the growth axis. We do not observe extended structural defects (stacking faults or dislocations) introduced by the epitaxial process. Low-temperature ISB absorption from 1.5 to 9 THz (6.3–37.4 meV) is demonstrated, covering most of the 7–10 THz band forbidden to GaAs-based technologies.